DAMPAK SITUASI SEBELUM DAN SAAT MEMANASNYA KONFLIK RUSIA UKRAINA TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ketut Tanti Kustina; I Putu Vicky Suryadharma (Journal of Applied Management and Accounting Science, 2023)
The growth of the stock price index is one way to see the condition of the capital market. The Russia Ukraine conflict had a huge impact on global markets. This study aims to determine the difference in stock prices before and during the heating up of the Russia-Ukraine conflict in mining sector. The method used in this research is a quantitative method. The population in this study are mining sector companies listed on (IDX). The sampling technique used is a purposive sampling technique. With sample of 59 mining companies. Based on the normality test of different tests for the hypothesis used is the Wilcoxon signed rank test, significance value of .000, which means the hypothesis in this study is accepted. This study concludes that there is a significant difference in stock prices 3 months before and 3 months after the Russia-Ukraine conflict occurred in mining companies listed on the IDX.